1992
DOI: 10.1159/000294873
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Noradrenaline, Dopamine and Serotonin Contents in Follicular Fluid of Human Graafian Follicles after Superovulation Treatment

Abstract: We measured the noradrenaline (NA), serotonin (5-HT) and dopamine (DA) contents of 47 normally maturated and 16 cystically degenerated follicular fluid samples obtained from patients involved in the in vitro fertilization and gamete transfer program. The patients were given human menopausal gonadotropin (HMG), as a superovulation treatment, and 7,500 IU human chorionic gonadotropin (HCG) to induce ovulation 34–36 h prior to the follicular puncture done by laparoscope. The NA content of the normally developed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 2 publications
1
32
0
Order By: Relevance
“…The innervation of the ovary by adrenergic and cholinergic nerves has been well documented [5][6][7]. Other studies [8] showed that preovulatory human FF contains noradrenaline, dopamine and serotonin. In an in vitro cell culture system, serotonin exhibited a significant stimulatory effect on PG secretion by human GCs [2].…”
Section: Discussionmentioning
confidence: 92%
“…The innervation of the ovary by adrenergic and cholinergic nerves has been well documented [5][6][7]. Other studies [8] showed that preovulatory human FF contains noradrenaline, dopamine and serotonin. In an in vitro cell culture system, serotonin exhibited a significant stimulatory effect on PG secretion by human GCs [2].…”
Section: Discussionmentioning
confidence: 92%
“…Noradrenaline has been reported to modulate ovarian steroidogenesis [131][132][133][134][135][136][137] instead of stimulating ovulation. These effects of noradrenaline probably are mediated by both a-and b-adrenergic receptors located in the ovary [131][132][133][134]137].…”
Section: Steroidogenesismentioning
confidence: 99%
“…Tyrosine hydroxylase (TH) expression, a hallmark of dopaminergic and noradrenergic neurons, is found in the human fetal brain before all cortical layers have been formed [4][5][6], suggesting that at this early age DA is involved in proliferation, migration, and differentiation of young neurons [7][8][9]. Ambient DA was detected in follicular fluid of superovulated women [10], and human fetal brain tissue (9-10 gestational weeks [GWs]) in vitro [11]. All together, these findings imply that human neurodifferentiation may be regulated by DA.…”
Section: Introductionmentioning
confidence: 99%